Byzantium : beyond the cliche : A Conversation with Maria Mavroudi. - Burton, Howard (Toronto : Open Agenda Publishing, 2020)
This book is based on an in-depth filmed conversation between Howard Burton and Maria Mavroudi, Professor of History at UC Berkeley. Maria Mavroudi specializes in the study of the Byzantine Empire and this wide-ranging conversation provides a detailed exploration of her extensive research on the Byzantine Empire and how it has repeatedly been undervalued by historians despite having been a military and cultural powerhouse for more than a millennium.This carefully-edited book includes an introduction, Beyond the High-School Narrative, and questions for discussion at the end of each chapter. How.
Intro -- A Note on the Text -- Introduction -- The Conversation -- I. Becoming A Byzantinist -- II. Historical Background -- III. The High-School Narrative -- IV. Recovering Truth -- V. Building Knowledge -- VI. Annotated Discoveries -- VII. A Translational Discovery -- VIII. Arrows of Causality -- IX. Decline -- X. Extracting Meaning -- XI. Ever-Moving Targets -- Continuing the Conversation
Description based upon print version of record.
JSTOR
Keywords: Mavroudi, Maria V. -- Interviews; Byzantine Empire; Greece; Ancient; HISTORY; Rome; Medieval; Byzantine Empire; Interviews